Hollywood ending - Aronson, Letty 1943-; Allen, Woody 1935-; Allen, Woody 1935- (DreamWorks Home Entertainment, 2002)
Woody stars as Val Waxman, a neurotic, once great director who desperately needs a comeback vehicle to jump-start his fizzled career. But when opportunity finally knocks, it's his ex-wife Ellie - with the handsome, rich studio head she dumped him for-at the door!.